Effect of Different Sounds on Some Traits of Broiler Chick’s Meat - Rashid, Saman Abdulmajid; Khidhir, Zaid Khalaf; Abulateef, Salwan Mahmood; Abulateef, Firas Mahmood (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was conducted This study was carry out at the field of the Department of Animal Sciences, College of Agricultural Sciences, Sulaimani University - Iraq, for study the effect of sound on meat traits and quality of meat. The chicks gotten from hatchery Kasha in the Taslojha. The sounds treatment choosing as follows: Control (T1 without sound), Movement of Feet (T2), Soft Sound Hens (T3), Chicks Care (T4) and hatched chicks, straight run (n = 160), were randomly distributed among, 4 treatments, with 4 replicates (2 male −2 female) per treatment and 10 chicks per replicate .The chicks exposure to sound from 1 day to 14 day old after hatching for 15 minutes. The results show: a significant difference (p<0.05) of experimental treatments (T2, T3 and T4) in moisture, protein, Fat, Ash, Water holding capacity (WHC) and pH percentage for thigh and breast compare with control treatment (T1). A significant difference (p<0.05) of experimental treatments (T2, T3 and T4) in on non-essential amino acids and essential amino acids in the thigh and breast.
Keywords: Sound; Broiler Chicken; Traits meat